Moxibution sebagai Alternatif Penanganan Letak Sungsang - Waslia, Dede (JURNAL KESEHATAN KARTIKA, 2021)
Breech pregnancy affects in the complications of childbirth that cause maternal death, where 3-4% of childbirth in Indonesia consists of breech position. Head birth in the breech location does not have a mechanism "Maulage" so it only has 8 minutes after the body is born, therefore it can cause a large infant death. Moxibustion is a traditional Chinese medicine to improve breech presentation by stimulating Zhiyin acupoint (Bladder67/BL-67) in the legs resulting in heating energy at the pelvic floor causing increased uterine contractility energy, causing the baby to move around and turn around. The purpose of this study was to analyze the influence of moxibution on breech position changes. Method: This research method is a pure experiment with post test control design approach. The sample in this study was pregnant women with breech position at 32 – 36 weeks gestation. Sample selection is done with simple randomized sampling. Results: the result of the study found the influence of moxibution therapy on the location of breech with a value of p.001. Pregnant women who are given moxibution therapy are all subjected to a change in the position of the breech into the head. Conclusion: Moksibution at the acupuncture point BL67 effective and safe to improve the position of breech when used at the gestational age of 32-36 weeks conducted daily for a minimum of 10 days.